Vastness as an Embodied Representation of Existential Concepts - Harmon-Vukić, Mary; Spitalnic, Kate (Journal for the Cognitive Science of Religion, 2024)
This project explores the nature of the representation of non-agentic qualities that are associated with the Christian God (e.g., peace, love, joy, existence, unity, etc.). Specifically, we propose that these existential words maintain an embodied representation that involves visuo-spatial vastness. In four experiments, participants saw an image followed by words and non-words. The words were either existential words (e.g., peace, hope, unity, joy, etc.) or positively-valenced abstract concepts (e.g., luck, wealth, success, fun, etc.). Participants indicated whether the string of letters was a word or not by pressing a “yes” or “no” key as quickly as possible. Response times were recorded. In Experiments 1 and 2, images of nature depicting visuo-spatial vastness or close-up images of nature, respectively, facilitated responses to existential words compared to control words. However, in Experiment 3, when the images were presented for a much briefer duration (i.e., 250 msecs), only vast images facilitated responses to existential words. Finally, Experiments 4A and 4B demonstrated that the priming effect between vast images and existential words varied as a function of posture. Specifically, the facilitation to existential words following vast images remained when participants maintained a vast posture (i.e., arms open) but was eliminated with a constricted posture (e.g., arms crossed). The overall pattern of results across the four experiments supports the notion that existential words are associated with visuo-spatial, and perhaps, proprioceptive vastness. The results hint at the possibility that vastness is an important component of the embodied representation of existential concepts and may also relate to the representation of the Christian God.